Island Bats: Evolution, Ecology, and Conservation - Fleming, Theodore H. (University Of Chicago Press, 2012)
"Island Bats will be of great interest to ecologists, biogeographers, conservation biologists in general, and bat biologists in particular - especially those interested in the biology of island faunas.